Structural response of corrugated plates under blast loading: The influence of the pressure-time history. (April 2021) - Caçoilo, A.; Mourão, R.; Teixeira-Dias, F.; Lecompte, D.; Rush, D.
Abstract: The propagation of shock waves in confined environments is a complex phenomenon due to the potential for a multiplicity of reflections, diffraction and superposition of waves. The study of such wave propagation effects, which is different from the propagation of shock waves in free-field scenarios, is not entirely described in literature, especially when studying their influence on the response of structures. The analysis of such phenomena is of extreme relevance to the evaluation of protective structures to ensure the security of equipment and personnel. This paper studies the influence of shock wave related parameters on the mechanical response of simple structural elements. This is achieved through the analysis of the impulse train, multiple positive and negative pressure profiles and signal simplifications. This research uses the finite element code LS-DYNA to analyse the structural response sensitivity of a metallic plate to different parameters, when subjected to pressure data recorded from experimental tests. It is observed that the structural response is significantly influenced by the loading regime. Results indicate that the impulse has a significant effect on the deflection-time history of the structure in the impulsive regime and that the peak pressure and pulse duration affect the deflection response in the dynamic regime. It also shows that correctly defining the negative impulse train in the pressure-time history is one of the main factors leading to an accurate modelling of the mechanical response of the structure. It is also found that a complex and realistic pressure history profile can be reduced to a simplified pulse for structural analysis and design purposes.